Impaired Wound Healing of Alveolar Lung Epithelial Cells in a Breathing Lung-On-A-Chip - Felder, Marcel; Trueeb, Bettina; Stucki, Andreas Oliver; Borcard, Sarah; Stucki, Janick Daniel; Schnyder, Bruno; Geiser, Thomas; Guenat, Olivier Thierry (Frontiers in Bioengineering and Biotechnology, 2019)
The lung alveolar region experiences remodeling during several acute and chronic lung diseases, as for instance idiopathic pulmonary fibrosis (IPF), a fatal disease, whose onset is correlated with repetitive microinjuries to the lung alveolar epithelium and abnormal alveolar wound repair. Although a high degree of mechanical stress (>20% linear strain) is thought to induce IPF, the effect of lower, physiological levels of strain (5–12% linear strain) on IPF pathophysiology remains unknown. In this study, we examined the influence of mechanical strain on alveolar epithelial wound healing. For this purpose, we adopted the “organ-on-a-chip” approach, which provides the possibility of reproducing unique aspects of the in vivo cellular microenvironment, in particular its dynamic nature. Our results provide the first demonstration that a wound-healing assay can be performed on a breathing lung-on-a-chip equipped with an ultra-thin elastic membrane. We cultured lung alveolar epithelial cells to confluence, the cells were starved for 24 h, and then wounded by scratching with a standard micropipette tip. Wound healing was assessed after 24 h under different concentrations of recombinant human hepatic growth factor (rhHGF) and the application of cyclic mechanical stretch. Physiological cyclic mechanical stretch (10% linear strain, 0.2 Hz) significantly impaired the alveolar epithelial wound-healing process relative to culture in static conditions. This impairment could be partially ameliorated by administration of rhHGF. This proof-of-concept study provides a way to study of more complex interactions, such as a co-culture with fibroblasts, endothelial cells, or immune cells, as well as the study of wound healing at an air–liquid interface.